The representation of Asian others in Korean cinema since 2003: multiculturalism, nationalism and sub-imperialism - Bae, Juyeon (2016)
This thesis elucidates current industrial and representational tendencies in South Korean films that depict Asian others. Asian others such as migrant workers, marriage migrants, overseas ethnic Koreans and North Korean defectors have become increasingly important in South Korean filmic discourse and practice since 2003. This thesis examines how contemporary Korean cinema has responded to the multicultural society and how it seeks to articulate Korean nationalism in the globalised era through the appropriation of Asian others. Such films are intertwined with governmental policies of multiculturalism and discourses on globalisation and thus reflect historical formations both inside and outside South Korean cinema. In particular, this thesis places the celebration of multicultural identity in Korean cinema into dialogue with existing debates on nationalism and sub-imperialism. Through case studies of selected films, this thesis investigates the tension between a changing society and emerging sub-imperial perspectives. The specific interest of this thesis lies in the examination of historical, geopolitical and socio-cultural trajectory in the representation of Asian others, since this discursive structure has been formed around Asia and its regional socio-political history. In doing so, this thesis aims to shift the discursive sphere of these films, which is limited to the discussion of multiculturalism and globalisation, to an expanded sphere which embraces historical and regional perspectives.